The corporate saving glut and the current account in Germany - Thorsten Klug; Eric Mayer; Tobias Schuler (University of Würzburg, Department of Economics, 2019)
We investigate for the case of Germany the positive correlation between the corporate saving glut in the non-financial corporate sector and the current account surplus from a capital account perspective. By employing sign restrictions our findings suggest that mostly labor market, world demand and financial friction shocks account for the joint dynamics of excess corporate saving and the current account surplus. Household saving shocks, in contrast, cannot explain the correlation. We conclude that the corporate saving glut, explained through these factors, is the main driver of the current account surplus.
Keywords: E32; F32; F45; 330; current account; corporate saving; macro shocks